THE IMPORTANT ROLE OF SPORTS DEVELOPMENT IN IMPROVING THE PERFORMANCE OF INDONESIAN ATHLETES: A SYSTEMATIC LITERATURE REVIEW - Hidayat, Taufik (ASEAN Journal of Sport for Development and Peace, 2024)
National development in the field of sports, as regulated in Law Number 5 of 2005 concerning the National Sports System, aims to improve health, fitness, achievement and human quality, as well as instilling moral values, sportsmanship and discipline. This research aims to examine the important role of sports development in improving the performance of Indonesian athletes. The research method uses the PRISMA approach by collecting and analyzing literature from the Scopus and Google Scholar databases. The research results show that effective management, psychological development, adequate infrastructure, and public policy support are the main factors in improving athlete performance. Although there is great potential, obstacles such as lack of infrastructure, human resources and government support need to be overcome. Synergy between the government, KONI, academics, practitioners and society is very important to advance sports and produce outstanding athletes in the future.